2016
DOI: 10.1093/jtm/tav008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors associated with acute mountain sickness in children trekking on Jade Mountain, Taiwan

Abstract: The incidence of AMS in children trekking on Jade Mountain is greater than that observed in adults, and was associated with altitude and recent URI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
2
19
1
Order By: Relevance
“…We found that up to 74.6% of children had sleep disturbance during the trip ( Table 2 ), which was a higher rate than in other studies [ 8 , 22 , 24 ]. Similar findings were also reported in children and adult trekkers on Jade Mountain (3,952 m) [ 15 , 25 ]. This may be due to the crowded environment of Qika Hut and Sanliujiu Hut, which contain a maximum of 130 and 110 people, respectively, in two large rooms.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We found that up to 74.6% of children had sleep disturbance during the trip ( Table 2 ), which was a higher rate than in other studies [ 8 , 22 , 24 ]. Similar findings were also reported in children and adult trekkers on Jade Mountain (3,952 m) [ 15 , 25 ]. This may be due to the crowded environment of Qika Hut and Sanliujiu Hut, which contain a maximum of 130 and 110 people, respectively, in two large rooms.…”
Section: Discussionsupporting
confidence: 87%
“…Most studies found no difference in AMS incidence between males and females [ 4 , 14 15 , 21 , 25 , 29 ], while some studies reported that female sex was more susceptible to the development of AMS [ 8 , 13 , 20 , 24 , 27 28 ]. However, our study showed that males had a significantly higher incidence of AMS than females ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMS is more likely to happen at altitudes higher than 2500 m, 4 and worldwide studies reported an incidence of AMS of 25%–37% at 1900–3400 m. 1 5 Children are more prone to develop AMS, with an incidence of 59%. 6 …”
Section: Introductionmentioning
confidence: 99%